The SphK1/S1P axis regulates morphology and cell-cell interactions of retina pigment epithelium cells - Torlaschi, Camila (2025)
Sphingosine-1-phosphate (S1P), a bioactive sphingolipid, regulates multiple key cellularprocesses. We demonstrated that S1P promotes migration and proinflammatory cytokine releasein retinal pigment epithelium (RPE) cells. These cells provide the retina with a physical andmetabolic barrier, the disruption of which contributes to the onset of numerous retinopathies.We now investigated whether S1P controlled RPE morphology and cell-cell interactions. Treatmentof human RPE cell line (ARPE-19) cultures with PF543, a sphingosine kinase-1 (SphK1) inhibitor,decreased cell migration in confluent cultures. In sub-confluent cultures, PF543 inducedcell retraction and the occurrence of elongated, spindle-like cells, absent in controls. PF543 inducedsimilar morphological changes in D407 RPE cell line. S1P preserved cell morphology inPF543-treated cultures, reducing the presence of spindle-like cells. Clusters of paxillin and talin,focal adhesion components, virtually disappeared from cell periphery in PF543-treated cells butwere preserved upon S1P addition. While PF543 decreased fibronectin expression and promotedZO-1 delocalization from the cell membranes, S1P prevented these changes. Pretreatment withW146 and JTE013, S1P1 and S1P2 antagonists, respectively, before adding PF543 and S1P, partiallyblocked S1P preservation of cell morphology, whereas incubation with BML-241, a S1P3antagonist, had no effect, implying that activation of S1P1 and S1P2 was required for S1P effect.In control cells, morphology was not affected either by the addition of S1P1, S1P2 and S1P3 antagonistsor by inhibiting the export of S1P with an inhibitor for Spinster-2, its major transporter,suggesting that endogenous S1P preservation of morphology did not involve ?inside-out?signaling. Our results suggest that SphK1 activity and exogenous S1P were required for controllingRPE cytoskeletal changes and cell interactions, essential for preserving its barrier function.